The Urgency of Artificial Intelligence Regulation in Supporting the National Defence System - Pangestu, Ilham Aji; Thorik, Achmad; Fadhlillah, Muhammad Rizqi; Mozin, Nopiana (Universitas Negeri Gorontalo, 2024)
This research analyzes the urgency of regulating Artificial Intelligence in supporting the national defense system. This research is a perspective normative legal research. The approaches used include the Legislation approach and the comparative approach. Legal materials consist of primary and secondary legal materials. Legal materials are obtained through library studies. Analysis of legal materials is done through deductive syllogism. Based on the discussion results, it is known that first, the use of Artificial Intelligence in strengthening the national defense system is increasingly developed by countries worldwide. Second, Indonesia still needs to be more optimal in using Artificial Intelligence technology to enhance the national defense system. Third, Indonesia still needs laws and regulations that specifically regulate the use of Artificial Intelligence in the national defense system. Researchers provide suggestions, including, first, forming laws and regulations that specifically restrict the use of Artificial Intelligence in the national defense system. Second, strengthening the position of institutions that specifically handle and are responsible for using Artificial Intelligence in the national defense system. Third, enhancing the capacity and capability of human resources in utilizing Artificial Intelligence in the national defense system. Fourth, prioritize Artificial Intelligence in national defense by allocating the special defense budget.